Prophylactic ondansetron eight milligrams versus four milligrams against post spinal anaesthesia shivering - Kumar, Ajay; Singh, Anuj; Sharma, Shamabhu P.; Dutta, Amitava; Sharma, Amit Kumar (International Surgery Journal, 2021)
Background: Shivering is one of the commonly encountered adverse affect after spinal anaesthesia. Shivering can be very discomforting to the patient and hampers operative maneuvering. Pharmacological therapies have been studied for control and management of shivering. One such drug is ondansetron, a 5-HT3 antagonist. Aim of current study is to evaluate the efficacy of prophylactic administration of ondansetron 8 mg vs. 4 mg for prevention of shivering. Methods: A prospective, randomized, and double blind study was conducted on 100 patients, from either gender, aged 20-60 years, of the American society of anesthesiologists grade I or II, scheduled for various surgeries under spinal anesthesia. The patients were randomly divided into two groups of 50 each to receive either ondansetron 8 mg (group E) or ondansetron 4 mg, (group F) as slow intravenous infusion prior to spinal anesthesia. The primary end point were intraoperative shivering and secondary outcomes included hypotension, adverse reaction, cardiac dysrhythmia’s. Results: A total of 10 patients in group E (20%) and 20 (40%) patients in group F experienced shivering (p=0.029). Incidence of nausea was similar in both groups, total of 8 (16%) patients in group E and 5 (10%) in group B had hypotension (p=0.27). 1 (2%) patient in group E experienced bradycardia. Conclusions: Prophylactic administration of ondansetron 8 mg has better efficacy in prevention of spinal anaesthesia induced shivering with minimal side effects as compared to 4 mg dosage.